2011
DOI: 10.2478/s13545-011-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Chaetoceros resting spores as indicators of Holocene paleoenvironmental changes in the Gulf of Gdańsk, southern Baltic Sea

Abstract: The aim of this study was to analyze resting spores of Chaetoceros spp. preserved in Middle and Late Holocene sediments of the three parts of the Gulf of Gdańsk, southern Baltic Sea. The material studied consists of ten cores retrieved from Kuźnica Deep (Puck Lagoon), as well as the shallower and deeper parts of the Outer Puck Bay region. Our results indicate that the abundance of Chaetoceros resting spores in diatom taphocoenoses corresponded to regional and local paleoecological changes registered in Mastogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Previous studies on the diatom Skeletonema have shown that the morphology of the resting cells and germinated cells is indistinguishable (Itakura et al 1992), whereas the resting and germinated spores of Chaetoceros species can be distinguished based on morphology. Therefore, the ability to identify Chaetoceros species from the morphology of viable germinated recent and ancient resting spores of Chaetoceros will improve the scope of paleoecological studies (Witak et al 2011). To the best of our knowledge this is the first study reviving thousands of years old (~7200-1000 cal yr BP) diatoms from dated sediments.…”
Section: Sanger Sequencing Of Dna From Unialgal Cultures Of Recent Rementioning
confidence: 95%
See 3 more Smart Citations
“…Previous studies on the diatom Skeletonema have shown that the morphology of the resting cells and germinated cells is indistinguishable (Itakura et al 1992), whereas the resting and germinated spores of Chaetoceros species can be distinguished based on morphology. Therefore, the ability to identify Chaetoceros species from the morphology of viable germinated recent and ancient resting spores of Chaetoceros will improve the scope of paleoecological studies (Witak et al 2011). To the best of our knowledge this is the first study reviving thousands of years old (~7200-1000 cal yr BP) diatoms from dated sediments.…”
Section: Sanger Sequencing Of Dna From Unialgal Cultures Of Recent Rementioning
confidence: 95%
“…By reviving resting spores deposited in sediments and extracting DNA from them we have demonstrated that Chaetoceros muelleri resting spores provide a promising model system for understanding species adaption and evolution across geological timescales and address questions about the impact of human-induced perturbations on life on Earth. Furthermore, previous attempts to use resting spores for paleoenvironmental reconstructions by assigning them to species met with limited success as most of the resting spores are hard to classify (Ishii et al 2011;Witak et al 2011), severely hindering our understanding of paleoproductivity and the effect of environmental change on species. We revived several Chaetoceros species but we cultured only C. muelleri in this study.…”
Section: Sanger Sequencing Of Dna From Unialgal Cultures Of Recent Rementioning
confidence: 99%
See 2 more Smart Citations
“…It was observed to be one of the most frequently occurring genus among centric diatoms (Nwankwo & Onyema 2003, Tabassum & Saifullah 2010. Records of Chaetoceros have also been well observed in sediments with special reference to their resting spores (Stockwell 1991, Witak et al 2011, Ferrario et al 1998, Moazzam & Baig 1994. Variation in physiological behavior and their responses to hydrological parameters have also been studied (Johansen et al 1990).…”
Section: Introductionmentioning
confidence: 99%